AKTIVITAS DAKWAH BIL HAL PENGURUS MASJID NURUL HAQ DI JORONG PATOMUAN KECAMATAN TALAMAU KABUPATEN PASAMAN BARAT - Januardi Januardi (Jurnal Komunikasi, 2023)
Da'wah is the activity of inviting people to the path outlined by Allah SWT. In achieving success in Islamic da'wah activities, there are many da'wah activities that can be chosen and one of them is the method given by Rasulullah SAW and his friends, namely direct demonstration, this da'wah activity is called da'wah bil hal. Da'wah bil is an Islamic da'wah activity carried out with real action towards the needs of the recipient of the da'wah. Da'wah bil hal is a da'wah activity aimed at improving the welfare and happiness of people's lives, both spiritual and physical. The aim of the research is to provide an overview of the application of da'wah bil activities for the administrators of the Nurul Haq mosque in Jorong Patomuan, Talamau District, West Pasaman Regency. The method used in this study is a qualitative approach, which is a field survey and is descriptive in nature. Data collection methods used by the author in this study are observation, documentation and interviews